Obesity code: Unlocking the secrets of weight loss - Fung, Jason; Noakes, Timothy (fwd.) (Mumbai Yogi Impressions, 2016)
foreword by TIMOTHY NOAKES THE OBESITY CODE Why your body$1 (Bs own insulin is the key to controlling your weight UNLOCKING THE SECRETS OF WEIGHT LOSS Everything you believe about how to lose weight is wrong. Weight gain and obesity are driven by hormones$1 (Bin everyone$1 (Band only by understanding the effects of insulin and insulin resistance can we achieve lasting weight loss. (3z(BNot only full of insights, but also surprisingly funny. Read it to understand why the world became fat, how to reverse the epidemic$1 (Band how to stay thin yourself.(3y (BAndreas Eenfeldt, MD Founder of Dietdoctor.com (3z(BFung zeroes in on why insulin resistance has become so prevalent and specific outside-the-box solutions that have emerged as the key to maximizing health.(3y (BJimmy Moore Author of Keto Clarity and Cholesterol Clarity In this highly readable and provocative book, Dr. Jason Fung sets out an , robust theory of obesity that provides startling insights into proper nutrition. In addition to his five basic steps, a set of lifelong habits that will improve your health and control your insulin levels, Dr. Fung explains how to use intermittent fasting to break the cycle of insulin resistance and reach a healthy weight$1 (Bfor good.s
Keywords: Healthcare; Obesity